2013
DOI: 10.1073/pnas.1215840110
|View full text |Cite
|
Sign up to set email alerts
|

B cells promote inflammation in obesity and type 2 diabetes through regulation of T-cell function and an inflammatory cytokine profile

Abstract: Patients with type 2 diabetes (T2D) have disease-associated changes in B-cell function, but the role these changes play in disease pathogenesis is not well established. Data herein show B cells from obese mice produce a proinflammatory cytokine profile compared with B cells from lean mice. Complementary in vivo studies show that obese B cell-null mice have decreased systemic inflammation, inflammatory B-and T-cell cytokines, adipose tissue inflammation, and insulin resistance (IR) compared with obese WT mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
442
5
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(484 citation statements)
references
References 39 publications
17
442
5
7
Order By: Relevance
“…These studies showed that if depletion of CD11c + macrophages or inhibition of macrophage recruitment via MCP-1 knockout in obese mice could significantly reduce inflammation and increase insulin sensitivity (Kamei et al, 2006;Kanda et al, 2006;Patsouris et al, 2008). Increasing evidence in animals and humans about inflammation-induced insulin resistance in T2D were provided, and included abnormalities of lymphocytes (DeFuria et al, 2013;Winer et al, 2011), neutrophils (Talukdar et al, 2012), eosinophils , mast cells (Liu et al, 2009) and dendritic cells (Musilli et al, 2011). Therefore, the biggest challenge for treatment of T2D was modifying these immune cells to repair the insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that if depletion of CD11c + macrophages or inhibition of macrophage recruitment via MCP-1 knockout in obese mice could significantly reduce inflammation and increase insulin sensitivity (Kamei et al, 2006;Kanda et al, 2006;Patsouris et al, 2008). Increasing evidence in animals and humans about inflammation-induced insulin resistance in T2D were provided, and included abnormalities of lymphocytes (DeFuria et al, 2013;Winer et al, 2011), neutrophils (Talukdar et al, 2012), eosinophils , mast cells (Liu et al, 2009) and dendritic cells (Musilli et al, 2011). Therefore, the biggest challenge for treatment of T2D was modifying these immune cells to repair the insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity promotes changes in adipose tissue metabolism, such as increased rate of spontaneous (basal) lipid mobilisation (lipolysis) from fat cells, as well as alterations in populations of adipose tissue-residing immune cells. Data in both animal models [1,2] and human obese WAT [3,4] have suggested an increased recruitment and/or differentiation of pro-inflammatory immune cell types (predominantly M1 macrophages) and also, albeit to a less pronounced degree, Electronic supplementary material The online version of this article (doi:10.1007/s00125-015-3810-6) contains peer-reviewed but unedited supplementary material, which is available to authorised users.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging concept that activation of the adaptive immune system links obesity to metabolic disease has led our group and others to examine the role of leukocyte cross talk in adipose tissue inflammation [14,[40][41][42][43]. T cell costimulation is important in APC-T cell communication, and these signals are often critical nodes in the regulation of both T reg and effector/ memory T conv activity and homeostasis [18,44,45].…”
Section: Discussionmentioning
confidence: 99%